ANALISIS KEPEMIMPINAN KEPALA SEKOLAH DALAM MEWUJUDKAN MERDEKA BELAJAR - Annisa Husniya; Putri Andini; Hutni Soraya lubis; Amin Harahap (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
This study aims to examine the role of principal leadership in the implementation of the Independent Curriculum in educational units. The Independent Curriculum, initiated by the Ministry of Education, Culture, Research, and Technology, is designed to encourage the creation of a more flexible, contextual, and innovative learning process, by providing greater autonomy for teachers and students in learning activities. The method used in this study is a Systematic Literature Review (SLR) through an analysis of ten articles sourced from national journals and published in the 2022–2023 period, focusing on principal leadership and the implementation of the Independent Curriculum. The results of the study indicate that principal leadership has a significant influence on the successful implementation of the Independent Curriculum in schools. Principals play a crucial role in building teacher motivation and capacity to conduct relevant and meaningful learning, providing supporting facilities and infrastructure, strengthening the active participation of students and parents, and establishing collaboration with various stakeholders. The findings of this study are expected to serve as a reference for principals in determining strategies, patterns, and leadership styles that are appropriate to the needs and characteristics of their respective schools.ABSTRAKPenelitian ini bertujuan untuk menelaah peran kepemimpinan kepala sekolah dalam pelaksanaan Kurikulum Merdeka di satuan pendidikan. Kurikulum Merdeka yang digagas oleh Kementerian Pendidikan, Kebudayaan, Riset, dan Teknologi dirancang untuk mendorong terciptanya proses pembelajaran yang lebih fleksibel, kontekstual, dan inovatif, dengan memberikan ruang otonomi yang lebih luas bagi guru dan peserta didik dalam kegiatan belajar. Metode yang digunakan dalam penelitian ini adalah Systematic Literature Review (SLR) melalui analisis terhadap sepuluh artikel yang bersumber dari jurnal nasional dan dipublikasikan pada periode 2022–2023, dengan fokus pada kepemimpinan kepala sekolah serta implementasi Kurikulum Merdeka. Hasil kajian menunjukkan bahwa kepemimpinan kepala sekolah memiliki pengaruh yang signifikan terhadap keberhasilan penerapan Kurikulum Merdeka di sekolah. Kepala sekolah berperan penting dalam membangun motivasi dan kapasitas guru untuk menyelenggarakan pembelajaran yang relevan dan bermakna, menyediakan sarana dan prasarana pendukung, menguatkan partisipasi aktif peserta didik dan orang tua, serta menjalin kerja sama dengan berbagai pemangku kepentingan. Temuan penelitian ini diharapkan dapat menjadi referensi bagi kepala sekolah dalam menentukan strategi, pola, dan gaya kepemimpinan yang sesuai dengan kebutuhan serta karakteristik sekolah masing-masing.